2004
DOI: 10.1590/s0100-83582004000400018
|View full text |Cite
|
Sign up to set email alerts
|

Lixiviação de herbicidas no solo aplicados com água de irrigação em plantio direto

Abstract: RESUMO -O objetivo deste trabalho foi avaliar a lixiviação no solo dos herbicidas metolachlor e fomesafen aplicados com água de irrigação de pivô central, nos plantios direto (palha de milho e de plantas daninhas) e convencional, na cultura do feijão (Phaseolus vulgaris) em um Argissolo Vermelho-Amarelo câmbico. Foi conduzido um experimento, com três repetições, no qual o metolachlor (2,4 kg ha -1 ) foi aplicado, em pré-emergência, com lâminas de água de 5, 10 e 15 mm, e o fomesafen (0,225 kg ha -1 ), em pós-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
7

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
0
6
1
7
Order By: Relevance
“…That is, the control of the weed when the crop residue amount was 14 t ha -1 was 58% and at 10 t ha -1 was 85% at 94 and 92 DAA. Contrary to the observations made in this experiment, when bean was directly sown under corn crop residue, the herbicide metolachlor was not detected 15 days after its application in any of the soil layers (0-5, 5-10, and 10-15 cm) submitted to analysis (Fontes et al, 2004). Teasdale et al (2003) also verified metolachlor to be present in lower initial concentrations in the soil solution when the herbicide had been sprayed over the residue of Vicia villosa, which resulted in the poor control of Panicum dichotomiflorum.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…That is, the control of the weed when the crop residue amount was 14 t ha -1 was 58% and at 10 t ha -1 was 85% at 94 and 92 DAA. Contrary to the observations made in this experiment, when bean was directly sown under corn crop residue, the herbicide metolachlor was not detected 15 days after its application in any of the soil layers (0-5, 5-10, and 10-15 cm) submitted to analysis (Fontes et al, 2004). Teasdale et al (2003) also verified metolachlor to be present in lower initial concentrations in the soil solution when the herbicide had been sprayed over the residue of Vicia villosa, which resulted in the poor control of Panicum dichotomiflorum.…”
Section: Resultscontrasting
confidence: 99%
“…The adsorption by plant residues is dependent on their degree of decomposition and age (Mersie et al, 2006). Studies with metolachlor have reported its possible retention by plant residues and thus reduced efficacy (Oliveira et al, 2001;Teasdale et al, 2003;Fontes et al, 2004). The time interval between herbicide application and the first rains is another important factor: depending on how long that period is, the chances of herbicide loss by physical (such as volatilization) or chemical (such as photo degradation and adsorption) processes will be higher or lower.…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Weber et al (1993), a baixa mobilidade do fomesafen no solo pode ser atribuída à sua sorção aos colói-des orgânicos e minerais do solo, apesar de sua elevada solubilidade em água e Koc baixo (60 mL g -1 solo). Em estudo com o objetivo de avaliar a lixiviação do fomesafen aplicado por via da água de irrigação em plantio direto, Fontes et al (2004) verificaram que ele foi lixiviado até 10 cm de profundidade já aos 15 dias após a herbigação. Esse estudo foi conduzido em solo com 49% de argila e 2,83 dag kg -1 de matéria orgânica.…”
Section: Resultsunclassified
“…Esse fato evidenciou atividade microbiana superior no solo cultivado no SPD, o que pode ser atribuído ao não-revolvimento do solo e à manutenção de uma camada de palha na sua superfície. Diversos trabalhos já confirmaram a maior atividade microbiana no SPD, comparado ao SPC (Amato & Ladd, 1992;Carter, 1992;Balota et al, 2003;Fontes et al, 2004;FEBRAPDP, 2005).…”
Section: Resultsunclassified